2011
DOI: 10.1021/jp110297q
|View full text |Cite
|
Sign up to set email alerts
|

Crystallization Kinetics and Excess Free Energy of H2O and D2O Nanoscale Films of Amorphous Solid Water

Abstract: Temperature-programmed desorption (TPD) and reflection absorption infrared spectroscopy (RAIRS) are used to investigate the crystallization kinetics and measure the excess free energy of metastable amorphous solid water films (ASW) of H(2)O and D(2)O grown using molecular beams. The desorption rates from the amorphous and crystalline phases of ASW are distinct, and as such, crystallization manifests can be observed in the TPD spectrum. The crystallization kinetics were studied by varying the TPD heating rate f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

19
135
3

Year Published

2013
2013
2023
2023

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 84 publications
(157 citation statements)
references
References 79 publications
19
135
3
Order By: Relevance
“…Since the pre-exponential factor is not reported in Baragiola et al (2009) it is not possible to comment on the small difference in the crystallization activation energy. Moreover, Mate et al (2012) found that if the crystallization rate constants for ASW ice deposited at different temperatures were the same, the Avrami n parameters would be different, close to 1 for ice samples generated at 14 K. Extrapolating Smith et al (2011) data at 100 K gives a crystallization rate of 10 13 s −1 , which is close to our measurement range for diffusion at this temperature. Jenniskens et al (1995) demonstrated the phase change between the high-density amorphous ice (I ah ) obtained after deposition at 15 K and the lowdensity amorphous ice (I al ).…”
Section: Measurement Of the Asw Ice Film Reorganization Ratesupporting
confidence: 84%
See 4 more Smart Citations
“…Since the pre-exponential factor is not reported in Baragiola et al (2009) it is not possible to comment on the small difference in the crystallization activation energy. Moreover, Mate et al (2012) found that if the crystallization rate constants for ASW ice deposited at different temperatures were the same, the Avrami n parameters would be different, close to 1 for ice samples generated at 14 K. Extrapolating Smith et al (2011) data at 100 K gives a crystallization rate of 10 13 s −1 , which is close to our measurement range for diffusion at this temperature. Jenniskens et al (1995) demonstrated the phase change between the high-density amorphous ice (I ah ) obtained after deposition at 15 K and the lowdensity amorphous ice (I al ).…”
Section: Measurement Of the Asw Ice Film Reorganization Ratesupporting
confidence: 84%
“…We have extended the works of Mate et al (2012), Smith et al (2011) and Baragiola et al (2009) at lower temperatures using FTIR spectroscopy. We have deposited an ASW film at 15 K, set the ice film to a fixed temperature between 40 and 150 K, and monitored the change in the OH stretch band whose band shape is very sensitive to crystallization (Smith et al 2011), in order to measure the ASW crystallization kinetics.…”
Section: Measurement Of the Asw Ice Film Reorganization Ratementioning
confidence: 70%
See 3 more Smart Citations